Negative electrode active material, negative electrode including the same, and method for manufacturing the same
Patent Information
- Application Number
- CN202610087973.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-08
- Filing Date
- 2026-01-22
- Publication Date
- 2026-10-16
AI Technical Summary
[0011] For example, the combination of porous carbon support structures with high micropore or mesopore volumes, amorphous (e.g., non-crystalline) silicon deposition, and conformal carbon coatings provides a synergistic effect of enhanced lithium-ion diffusion, accommodating volume expansion during cycling, and improving or enhancing structural integrity. These features collectively contribute to enhanced electrochemical performance, including higher initial coulombic efficiency, enhanced cycle life, and increased specific capacity, thereby making the disclosed negative electrode active material and manufacturing method suitable for high-performance rechargeable lithium batteries.
Smart Images

Figure CN122930856A_ABST
Abstract
Description
[0001] This application claims priority and benefit to Korean Patent Application No. 10-2025-0045483, filed on April 8, 2025, with the Korean Intellectual Property Office, the entire disclosure of which is incorporated herein by reference. Technical Field
[0002] One or more embodiments of this disclosure relate to a negative electrode active material, a negative electrode including the negative electrode active material, and a method for manufacturing the negative electrode active material. Background Technology
[0003] Recently, with the rapid proliferation and widespread adoption of battery-powered electronic devices (such as mobile phones, laptops, etc.) and / or electric vehicles, the demand for rechargeable batteries with high energy density and large capacity (e.g., electrical capacity) has increased significantly. In response, extensive research and development efforts have been undertaken to enhance (e.g., improve) the performance of rechargeable lithium batteries.
[0004] A rechargeable lithium-ion battery includes a positive electrode, a negative electrode, and an electrolyte. Both the positive and negative electrodes (e.g., simultaneously) contain active (e.g., electroactive) materials capable of inserting and deintercalating lithium ions. As lithium ions move between the electrodes during charging and discharging (during charge and discharge cycles), electrical energy is generated through oxidation and reduction reactions. Summary of the Invention
[0005] One or more aspects of embodiments of this disclosure relate to negative electrode active materials exhibiting high capacity (e.g., electrical capacity), high efficiency (e.g., initial efficiency) and excellent or suitable cycle life characteristics, and negative electrodes comprising such negative electrode active materials.
[0006] One or more aspects of embodiments of this disclosure relate to methods for manufacturing negative electrode active materials.
[0007] Additional aspects of the embodiments will be set forth in part in the description which follows, and in part will be apparent from the description, or may be learned by practice of the disclosed embodiments.
[0008] According to one or more embodiments of this disclosure, the negative electrode active material may include a core and a carbon coating on the core. The core may include a porous carrier comprising a plurality of pores and silicon on the surface of the plurality of pores and the porous carrier. The plurality of pores may include micropores, wherein the volume ratio of the micropores of the porous carrier is from about 50% to about 100% relative to the total pore volume of the porous carrier, wherein the porous carrier may include a first amorphous (e.g., non-crystalline) carbon, and the silicon may include amorphous (e.g., non-crystalline) silicon.
[0009] According to one or more embodiments of this disclosure, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, which may include a core and a carbon coating disposed on the core, and the core may include a porous carrier comprising a plurality of pores and silicon disposed on the surface of the plurality of pores and the porous carrier. The negative electrode active material may include mesopores, and the volume ratio of mesopores in the negative electrode active material may be from about 50% to about 100% relative to (e.g., based on) the total pore volume of the negative electrode active material.
[0010] According to one or more embodiments of this disclosure, a method for manufacturing a negative electrode active material may include: preparing a porous support comprising a plurality of pores; performing a vapor deposition process on the porous support using a silicon precursor to form silicon; and forming a carbon coating in the product formed from the silicon using a carbon precursor. The plurality of pores may include micropores, and the volume ratio of micropores in the porous support may be from about 50% to about 100% relative to the total pore volume of the porous support.
[0011] For example, the combination of porous carbon support structures with high micropore or mesopore volumes, amorphous (e.g., non-crystalline) silicon deposition, and conformal carbon coatings provides a synergistic effect of enhanced lithium-ion diffusion, accommodating volume expansion during cycling, and improving or enhancing structural integrity. These features collectively contribute to enhanced electrochemical performance, including higher initial coulombic efficiency, enhanced cycle life, and increased specific capacity, thereby making the disclosed negative electrode active material and manufacturing method suitable for high-performance rechargeable lithium batteries. Attached Figure Description
[0012] The accompanying drawings, together with the specification, illustrate embodiments of the subject matter of this disclosure, and together with the description, serve to explain the principles of the embodiments of the subject matter of this disclosure.
[0013] Figure 1 This is a simplified conceptual diagram illustrating a rechargeable lithium battery according to one or more embodiments of the present disclosure.
[0014] Figures 2 to 5 Each of the above is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments of the present disclosure.
[0015] Figure 6 This is a cross-sectional view of the negative electrode for a rechargeable lithium battery according to one or more embodiments of the present disclosure.
[0016] Figure 7 This is a schematic diagram illustrating the negative electrode active material according to one or more embodiments of the present disclosure.
[0017] Figure 8This is a diagram illustrating a method for manufacturing a negative electrode active material according to one or more embodiments of the present disclosure.
[0018] Figure 9 It is a scanning electron microscope (SEM) image of the surface of the negative electrode active material according to Example 1 (performed on the surface of the negative electrode active material according to Example 1).
[0019] Figure 10A and Figure 10B It is a cross-sectional SEM image of the negative electrode active material based on Example 1.
[0020] Figure 11A and Figure 11B The results are based on the energy dispersive spectroscopy (EDS) line scan analysis of the negative electrode active material in Example 1.
[0021] Figure 12 It is based on the pore distribution diagram of the porous support and negative electrode active material in Example 1. Detailed Implementation
[0022] To fully understand the aspects and features of this disclosure, the subject matter will be described in more detail with reference to the accompanying drawings. However, this disclosure is not limited to the disclosed embodiments and may be implemented in one or more suitable forms. Rather, these embodiments are provided as examples with reference to the accompanying drawings to explain the aspects and features of this disclosure to those skilled in the art.
[0023] In this specification, if (for example, when) an element is described as "on" or "above" another element, it may be directly on or directly above another element, or there may be one or more intervening elements between them. Conversely, if (for example, when) an element is described as "directly on" or "directly above" another element, there are no intervening elements between them.
[0024] In the accompanying drawings, the thickness of one or more components may be exaggerated to better illustrate technical details. Throughout the specification, the same reference numerals denote the same elements in both the drawings and the written description, and their repeated description may be omitted in the specification.
[0025] As used herein, the singular forms “a,” “one,” and “the (said)” are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0026] Unless otherwise expressly stated in this specification, the singular form may also include the plural form.
[0027] Unless otherwise explicitly stated, the phrase “A or B” can mean “A but not B”, “B but not A”, and “A and B”.
[0028] In the context of this application, unless otherwise defined, the term “use” and its variations may be considered synonymous with the term “utilize” and its variations, respectively.
[0029] The terms “having / comprising” and their variations do not exclude the presence or addition of one or more other components. For example, it should be understood that the terms “comprising,” “including,” or “having,” specify the presence of the stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. Furthermore, the terms “comprising,” “including,” “having,” or similar terms include or support the terms “consisting of,” and “substantially consisting of,” indicating the presence of the stated features, integers, steps, operations, elements, and / or components, while other features, integers, steps, operations, elements, components, and / or groups thereof are absent or substantially absent.
[0030] Any numerical range described herein is intended to include all subranges of the same numerical precision contained within the described range. For example, the range “1.0 to 10.0” is intended to include all subranges between the described minimum value 1.0 and the described maximum value 10.0 (including both the described minimum value 1.0 and the described maximum value 10.0), such as having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit described herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit described in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to amend this specification (including the claims) to expressly describe any subranges contained within the range expressly described herein.
[0031] In this specification, the phrase "combination of them" may refer to mixtures, stacks, complexes, copolymers, alloys, blends, reaction products, etc. of the components.
[0032] Unless otherwise specifically defined, the term "particle size" refers to the average particle size. Particle size can also be expressed as the median particle size (D50), which corresponds to the diameter of 50% by volume of particles in the cumulative particle size distribution.
[0033] The average particle size (D50) can be measured using any suitable method that is generally available or commonly used, such as a particle size analyzer, transmission electron microscopy (TEM) images, and / or scanning electron microscopy (SEM) images. As used herein, unless otherwise defined (e.g., when), the average particle size refers to the diameter (D50) of the particles having a cumulative volume of 50% of the particle size distribution obtained by randomly measuring the size (e.g., diameter or major axis length) of approximately 20 particles in a scanning electron microscopy (SEM) image. In one or more embodiments, dynamic light scattering (DLS) can be used, in which particle counts across a size range are analyzed to calculate the average particle size (D50). Alternatively, laser scattering can be employed, in which target particles are dispersed in a solvent, introduced into a laser scattering particle measurement device (e.g., the MT 3000 from Microtrac), irradiated with ultrasound at 28 kHz and 60 W, and subsequently analyzed to determine the D50 value based on the 50% cumulative particle size distribution.
[0034] In one or more embodiments, if (e.g., when) the particles, pores, or grains are spherical (e.g., substantially spherical), "diameter" or "size" refers to the diameter of the particle, pore, or grain, and if (e.g., when) the particles, pores, or grains are non-spherical (e.g., substantially non-spherical), "diameter" or "size" refers to the length of the major axis.
[0035] It should be understood that even if the terms “about,” “approximately,” or “substantially” are not explicitly stated in a given element (e.g., a claim element), the scope of such an element is intended to include non-substantial variations or variations that would be understood by a person skilled in the art. For example, the numerical values and ranges provided herein are intended to include tolerances and measurement uncertainties that would be recognized by a person skilled in the art, and elements (e.g., claim elements) should be interpreted accordingly to cover such equivalents.
[0036] When describing embodiments of this disclosure, the word "may" means "one or more embodiments of this disclosure".
[0037] Figure 1 This is a simplified conceptual diagram illustrating a rechargeable lithium battery according to one or more embodiments of the present disclosure. (Refer to...) Figure 1 A rechargeable lithium battery may include a positive electrode 10, a negative electrode 20, a separator 30, and an electrolyte ELL.
[0038] The positive electrode 10 and the negative electrode 20 may be spaced apart and / or separated from each other (e.g., separated or isolated) by a diaphragm 30. The diaphragm 30 may be disposed between the positive electrode 10 and the negative electrode 20. The positive electrode 10, the negative electrode 20, and the diaphragm 30 may be in contact with the electrolyte ELL. The positive electrode 10, the negative electrode 20, and the diaphragm 30 may be immersed in the electrolyte ELL.
[0039] The electrolyte ELL can be the medium through which lithium ions transfer between the positive electrode 10 and the negative electrode 20. In the electrolyte ELL, lithium ions can move through the separator 30 toward one of the positive electrode 10 and the negative electrode 20.
[0040] Positive electrode 10 The positive electrode 10 for a rechargeable lithium battery may include a current collector COL1 and a positive electrode active material layer AML1 on the current collector COL1. The positive electrode active material layer AML1 may include a positive electrode active material and further include a binder and / or a conductive (e.g., electrically conductive) material (e.g., an electronic conductor).
[0041] For example, the positive electrode 10 may also include additives that can act as or be used as a sacrificial positive electrode.
[0042] The amount of positive electrode active material may be from about 90 wt% to about 99.5 wt% relative to (e.g., based on) 100 wt% of positive electrode active material layer AML1. The amount of each of the binder and conductive material may be from about 0.5 wt% to about 5 wt% relative to (e.g., based on) 100 wt% of positive electrode active material layer AML1.
[0043] The binder can improve or enhance the adhesion between the positive electrode active material particles or improve or enhance the adhesion between the positive electrode active material and the current collector COL1. The binder may include, for example, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin and / or nylon, but the embodiments disclosed herein are not limited thereto.
[0044] Conductive materials can be used to provide electrode conductivity (e.g., electrical conductivity) and any suitable conductive (e.g., electrically conductive) material that does not cause chemical changes (e.g., undesirable chemical changes) in a rechargeable lithium battery can be used as a conductive material. Conductive materials may include, for example: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers and / or carbon nanotubes; metal powders and / or metal fibers comprising one or more selected from copper, nickel, aluminum and silver; conductive (e.g., electrically conductive) polymers such as polyphenylene and / or polyphenylene derivatives; or mixtures thereof.
[0045] Aluminum (Al) can be used as a current collector COL1, but the embodiments disclosed herein are not limited thereto.
[0046] Positive electrode active material The positive electrode active material in the positive electrode active material layer AML1 may include compounds that can reversibly insert and deintercalate lithium (e.g., lithium intercalation compounds). For example, the positive electrode active material may include at least one type (class) of a composite oxide comprising lithium and a metal selected from cobalt, manganese, nickel and (e.g., any suitable) combinations thereof.
[0047] Composite oxides may include lithium transition metal composite oxides, such as lithium nickel oxides, lithium cobalt oxides, lithium manganese oxides, lithium iron phosphate compounds, cobalt-free lithium nickel manganese oxides, or combinations thereof (e.g., any suitable combination).
[0048] For example, the positive electrode active material may include a compound selected from the chemical formulas. Li a A 1-b X b O 2-c D c (Where, 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (Where, 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (Where, 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni 1-b-c Mn b X c O2-α D α (Where, 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni b Co c L 1 d G e O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0≤e≤0.1); Li a NiG b O2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); Li a CoG b O2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); Li a Mn 1-b G b O2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); Li a Mn2G b O4 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); Li a Mn 1-g G g PO4 (where 0.90 ≤ a ≤ 1.8 and 0 ≤ g ≤ 0.5); Li (3-f) Fe2(PO4)3 (where 0 ≤ f ≤ 2); and Li a FePO4 (where 0.90≤a≤1.8).
[0049] In the aforementioned chemical formula, A can be nickel (Ni), cobalt (Co), manganese (Mn), or a combination thereof (e.g., any suitable combination); X can be aluminum (Al), Ni, Co, Mn, chromium (Cr), iron (Fe), magnesium (Mg), strontium (Sr), vanadium (V), rare earth elements, or a combination thereof (e.g., any suitable combination); D can be oxygen (O), fluorine (F), sulfur (S), phosphorus (P), or a combination thereof (e.g., any suitable combination); G can be Al, Cr, Mn, Fe, Mg, lanthanum (La), cerium (Ce), Sr, V, or a combination thereof (e.g., any suitable combination); L 1 It can be Mn, Al, or any suitable combination thereof.
[0050] For example, the positive electrode active material can be a high-nickel positive electrode active material, wherein the nickel content of the high-nickel positive electrode active material is equal to or greater than about 80 mol%, equal to or greater than about 85 mol%, equal to or greater than about 90 mol%, equal to or greater than about 91 mol%, or equal to or greater than about 94 mol% and equal to or less than about 99 mol%, relative to 100 mol% of lithium-free metal in the lithium transition metal complex oxide. High-nickel positive electrode active materials can achieve high capacity (e.g., electrical capacity) and therefore can be used in rechargeable lithium batteries with high capacity (e.g., electrical capacity) and high density (e.g., energy density).
[0051] Diaphragm 30 Depending on the type of rechargeable lithium battery, the separator 30 may be present between the positive electrode 10 and the negative electrode 20. The separator 30 may include one or more of polyethylene, polypropylene and polyvinylidene fluoride, and may have multiple layers (such as polyethylene / polypropylene double-layer separator, polyethylene / polypropylene / polyethylene triple-layer separator and polypropylene / polyethylene / polypropylene triple-layer separator).
[0052] The diaphragm 30 may include a porous substrate and a coating located on one or both surfaces of the porous substrate (e.g., two opposite (oppositely facing) surfaces), the coating comprising an organic material, an inorganic material, or a combination thereof (e.g., any suitable combination).
[0053] The porous substrate may be a polymer layer selected from the following: polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and / or polytetrafluoroethylene (e.g., Teflon). TM Alternatively, it may be a copolymer or mixture of two or more materials as described in one or more embodiments.
[0054] Organic materials may include polyvinylidene fluoride copolymers and / or (meth)acrylic acid copolymers.
[0055] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, or any suitable combination thereof, but the embodiments of this disclosure are not limited thereto.
[0056] Organic and inorganic materials can coexist in a coating, or they can exist as a stack of coatings including organic materials and coatings including inorganic materials.
[0057] Electrolyte ELL Electrolytes (ELLs) used in rechargeable lithium batteries may include non-aqueous (e.g., water-insoluble) organic solvents and lithium salts.
[0058] Non-aqueous organic solvents can serve as or be used as a medium for transporting ions that participate in the electrochemical reactions of rechargeable lithium batteries.
[0059] Non-aqueous organic solvents may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or combinations thereof (e.g., any suitable combination).
[0060] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and / or butyl carbonate (BC).
[0061] Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valonate lactone, and / or caprolactone.
[0062] Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and / or tetrahydrofuran. Ketone solvents may include cyclohexanone. Alcohol solvents may include ethanol and / or isopropanol. Aprotic solvents may include: nitriles, such as R-CN (wherein R is a hydrocarbon group having a C2 to C20 straight-chain, branched, or cyclic structure, and may include double bonds (e.g., carbon-carbon double bonds), aromatic rings, and / or ether groups); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane and / or 1,4-dioxolane; and / or sulfolane.
[0063] Non-aqueous organic solvents can be used alone or in mixtures of two or more substances.
[0064] In one or more embodiments, if a carbonate solvent is used, cyclic carbonates and chain carbonates can be mixed and used, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.
[0065] Lithium salts can be materials dissolved in non-aqueous organic solvents to act as or serve as a source of lithium ions in rechargeable lithium batteries, enabling the rechargeable lithium battery to operate essentially and facilitating the movement of lithium ions between the positive and negative electrodes. Lithium salts can include, for example, those from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F 2y+1 At least one of the following: (SO2) (where x and y are integers from 1 to 20), lithium trifluoromethane sulfonate, lithium tetrafluoroethane sulfonate, lithium difluoro(oxalate)borate (LiDFOB), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0066] Rechargeable lithium batteries Based on their shape, rechargeable lithium batteries can be classified into cylindrical, prismatic, pouch-shaped, and coin-shaped types. Figures 2 to 5 Simplified diagrams are shown, each illustrating a rechargeable lithium battery according to one or more embodiments, wherein... Figure 2 A cylindrical battery is shown. Figure 3 A prismatic battery is shown. Figure 4 and Figure 5 The image shows pouch-type (types) batteries. (See reference.) Figures 2 to 4 The rechargeable lithium battery 100 may include an electrode assembly 40 in which a separator 30 is located between a positive electrode 10 and a negative electrode 20, and the rechargeable lithium battery 100 may further include a housing 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be immersed in an electrolyte. Figure 2 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of a sealed housing 50. In one or more embodiments, as Figure 3 As shown, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. Figure 4 and Figure 5 As shown, the rechargeable lithium battery 100 may include electrode terminals 70 or positive electrode terminals 71 and negative electrode terminals 72 that serve as electrical paths or act as electrical paths to guide current generated in the electrode assembly 40 to the outside.
[0067] The rechargeable lithium battery according to one or more embodiments of this disclosure can be used in automobiles, mobile phones and / or any other suitable electrical devices, but the embodiments of this disclosure are not limited thereto.
[0068] negative electrode 20 Figure 6 This is a cross-sectional view of the negative electrode for a rechargeable lithium battery according to one or more embodiments of the present disclosure. (Refer to...) Figure 6 According to one or more embodiments of the present disclosure, the negative electrode 20 may include a negative electrode current collector COL2 and a negative electrode active material layer AML2 on the negative electrode current collector COL2. The negative electrode active material layer AML2 may include a negative electrode active material and may also include a binder and / or a conductive (e.g., electrically conductive) material.
[0069] For example, the negative electrode active material layer AML2 may include about 90 wt% to about 99 wt% of negative electrode active material, about 0.5 wt% to about 5 wt% of binder, and about 0 wt% to about 5 wt% of conductive (e.g., electrically conductive) material.
[0070] The binder can improve or enhance the adhesion between the active material particles of the negative electrode, or improve or enhance the adhesion between the active material of the negative electrode and the negative electrode current collector COL2. The binder may include non-aqueous binders, aqueous binders, dry binders, or combinations thereof (e.g., any suitable combination).
[0071] Non-aqueous adhesives may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or any suitable combination thereof.
[0072] Waterborne adhesives may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluorinated elastomers, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resins, (meth)acrylic resins, phenolic resins, epoxy resins, polyvinyl alcohol, and combinations thereof (e.g., any suitable combinations).
[0073] If (for example, when) an aqueous binder is used as a negative electrode binder, it may further include a cellulose compound capable of providing or increasing viscosity. The cellulose compound may include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or an alkali metal salt thereof. The alkali metal may include sodium (Na), potassium (K), and / or lithium (Li).
[0074] Dry adhesives may include fibrillable polymeric materials such as polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof (e.g., any suitable combination).
[0075] Any suitable conductive material that can be used to provide electrode conductivity (e.g., electrical conductivity) and does not cause chemical changes (e.g., undesirable chemical changes) in a rechargeable lithium battery can be used as a conductive material. For example, conductive materials may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal powders and / or metal fibers, including copper, nickel, aluminum, and silver; conductive (e.g., electrically conductive) polymers such as polyphenylene and / or polyphenylene derivatives; or mixtures thereof.
[0076] The negative electrode current collector COL2 may include copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive (e.g., electrically conductive) metal, or any suitable combination thereof.
[0077] The negative electrode active material layer AML2 may include the negative electrode active material as described in one or more embodiments, and may also include crystalline carbon. The crystalline carbon may include artificial graphite, natural graphite, or combinations thereof (e.g., any suitable combination).
[0078] If (for example, when) the negative electrode active material layer AML2 comprises the negative electrode active material according to this disclosure as the first negative electrode active material and comprises crystalline carbon as the second negative electrode active material, then the weight ratio of the first negative electrode active material to the second negative electrode active material can be from about 1:99 to about 50:50. For example, the weight ratio of the first negative electrode active material to the second negative electrode active material can be from about 5:95 to about 40:60 or from about 10:90 to about 30:60. If the weight ratio of the first negative electrode active material to the second negative electrode active material satisfies the foregoing range, it can have the advantages of high capacity (e.g., electrical capacity), high output, and long lifetime.
[0079] Negative electrode active material AM Figure 7 This is a schematic diagram illustrating the negative electrode active material according to one or more embodiments of the present disclosure.
[0080] Reference Figure 7 The negative electrode active material AM according to one or more embodiments of this disclosure may include a core and a shell on the core. The core may include a porous support PMT and a silicon SCL. The shell may include a carbon-coated CTL.
[0081] Porous carrier PMTs can include carbon-based materials capable of reversibly inserting / deintercalating lithium ions. For example, porous carrier PMTs can include a first amorphous (e.g., non-crystalline) carbon. The first amorphous carbon can include at least one of activated carbon, carbon nanotubes, carbon nanowires, graphene, carbon fibers, furnace black, carbon black, acetylene black, superconducting acetylene black, Ketjen black, or any suitable combination thereof, but there is no particular limitation on the type (variety) of porous carrier PMTs.
[0082] For example, a porous support PMT may include activated carbon as hard carbon. Hard carbon can exhibit good or suitable electrical conductivity and lithium-ion mobility while experiencing minimal or reduced volume expansion during charging and discharging. Therefore, if (e.g., when) a porous support PMT includes hard carbon, volume expansion of silicon (Si) can be suppressed or reduced, and electrical conductivity and ionic conductivity can be improved.
[0083] The porous carrier PMT may include multiple pores (PORs) in its internal portion and surface. Because the porous carrier PMT includes multiple pores (PORs), these pores can act as or serve as buffers to accommodate the volume expansion of silicon. Therefore, the structure of the negative electrode active material (AM) can be maintained during charging and discharging, thereby improving or enhancing cycle life characteristics and achieving excellent or suitable initial efficiency. As a result, according to one or more embodiments of this disclosure, the volume expansion of rechargeable lithium batteries can be effectively or appropriately suppressed or reduced while utilizing the high capacity (e.g., electrical capacity) characteristics of silicon.
[0084] A multi-pore POR can include micropores. A multi-pore POR can also include mesopores and / or macropores. In this disclosure, a micropore can refer to a pore with a diameter of about 2 nm or less. A mesopore can refer to a pore with a diameter greater than about 2 nm and less than about 50 nm. A macropore can refer to a pore with a diameter of about 50 nm or more.
[0085] The volume ratio of micropores in a porous carrier PMT can be from about 50% to about 100% relative to the total pore volume of the porous carrier PMT. For example, the volume ratio of micropores in a porous carrier PMT can be from about 50% to about 95%, from about 60% to about 95%, or from about 60% to about 90% relative to the total pore volume of the porous carrier PMT.
[0086] The mesopore volume ratio of a porous carrier PMT can be about 40% or less relative to (e.g., based on) the total pore volume of the porous carrier PMT. For example, the mesopore volume ratio of a porous carrier PMT can be about 5% to about 40%, about 10% to about 40%, or about 10% to about 30%. The macropore volume ratio of a porous carrier PMT can be about 20% or less relative to (e.g., based on) the total pore volume of the porous carrier PMT. For example, the macropore volume ratio of a porous carrier PMT can be about 15% or less, about 12% or less, or about 10% or less. The total pore volume of a porous carrier PMT can be defined as the sum of the pore volumes of micropores, mesopores, and macropores within the porous carrier PMT as described in one or more embodiments.
[0087] If (e.g., when) the volume ratio of the micropores in the porous carrier PMT meets the aforementioned range, the size of the silicon SCL within the pore POR of the porous carrier PMT can be appropriately or suitably controlled or selected. For example, since the diameter of the micropores is about 2 nm or less, the size (e.g., diameter) of the silicon SCL within the micropores can be about 2 nm or less. Therefore, if (e.g., when) the volume ratio of the micropores is included in the aforementioned range, nanoscale silicon (e.g., silicon with suppressed or reduced volume expansion) having a size (e.g., diameter) of about 2 nm or less can be appropriately or suitably included in the negative electrode active material AM within the silicon SCL within the pore POR of the porous carrier PMT.
[0088] Conversely, if (for example, when) the volume ratio of micropores is less than about 50%, the volume ratio of mesopores to macropores becomes relatively high. Therefore, the area (or volume) occupied by macropores (e.g., the area within a porous carrier PMT where a silicon SCL can be deposited) may become relatively large, making it difficult to control the size of the silicon SCL. Consequently, the effect of suppressing or reducing the volume expansion of silicon may be limited, leading to a deterioration in the initial efficiency and cycle life characteristics of the rechargeable lithium-ion battery.
[0089] The average pore size of a porous support PMT can be greater than about 0 nm and less than or equal to about 10 nm. For example, the average pore size of a porous support PMT can be about 1 nm to about 8 nm, about 2 nm to about 8 nm, or about 3 nm to about 6 nm. The pore volume of a porous support PMT can be about 0.5 cm³. 3 / g to approximately 1cm 3 / g. For example, the pore volume of porous carrier PMT can be approximately 0.6 cm³. 3 / g to approximately 1cm 3 / g, approximately 0.7cm 3 / g to approximately 1cm 3 / g or approximately 0.8cm 3 / g to 1cm 3 / g.
[0090] If (for example, when) the average pore size and pore volume of the porous carrier PMT each meet the aforementioned ranges, the size of the silicon SCL deposited on the porous POR can be more appropriately or suitablely controlled or selected. Therefore, high capacity (e.g., capacitance) can be achieved while improving or enhancing initial efficiency and cycle life characteristics.
[0091] For example, the pore volume of the porous support PMT can be measured using the Barrett-Joyner-Halenda (BJH) method with N2 adsorption-desorption isotherms. For instance, a pretreatment process can be performed by heating the porous support PMT to approximately 523 K (Kelvin, absolute temperature) at a rate of approximately 10 K / min and maintaining the temperature at approximately 100 mmHg or lower for approximately 2 to approximately 10 hours. Subsequently, nitrogen can be adsorbed at approximately 32 points within a relative pressure (P / P0) range of approximately 0.01 torr to approximately 0.955 torr in liquid nitrogen adjusted to a relative pressure of approximately 0.01 torr or lower, followed by desorption at approximately 24 points until the relative pressure is approximately 0.14 torr. In this case, the pore size can be determined by the range of excess N2 adsorbed.
[0092] As another example, the volume ratios of mesopores and macropores to the total pore volume of the porous carrier PMT can be obtained using the Barrett-Joyner-Halenda (BJH) method with a porosity analyzer (ASAP2020, Micromeritics). In one or more embodiments, the volume ratio of micropores to the total pore volume of the porous carrier PMT can be determined using a t-plot method with the porosity analyzer (ASAP2020, Micromeritics).
[0093] The average particle size of the porous support PMT can be from about 1 μm to about 50 μm, from about 1 μm to about 30 μm, or from about 1 μm to about 20 μm. The average particle size can be the median particle size measured using a laser-type particle size analyzer. If (for example, when) the average particle size of the porous support PMT meets the aforementioned range, the negative electrode active material AM can exhibit excellent or suitable lithium-ion conductivity and electrical conductivity.
[0094] The amount of porous support PMT can be from about 30 wt% to about 80 wt% relative to the total weight of the negative electrode active material AM (e.g., based on 100 wt% of the negative electrode active material AM). For example, the amount of porous support PMT can be from about 40 wt% to about 70 wt%, from about 45 wt% to about 65 wt%, or from about 45 wt% to about 60 wt% relative to the total weight of the negative electrode active material AM (e.g., based on 100 wt% of the negative electrode active material AM). If (e.g., when) the amount of porous support PMT meets the foregoing range, it is feasible to limit the amount of silicon SCL to be deposited, thereby obtaining the advantage or benefit of ensuring the desired or suitable capacity (e.g., capacitance).
[0095] Silicon SCLs can be deposited on the surface of a porous carrier PMT and on multiple porous PORs. Although in Figure 7 The diagram shows a layer shape in which silicon SCLs are continuously formed, but embodiments of this disclosure are not limited thereto. Silicon SCLs may be formed in the form of discontinuously formed islands.
[0096] As described in one or more embodiments, a silicon SCL may comprise nanoscale silicon (Si) formed as pores (POR) on a porous carrier PMT. Silicon SCLs can be formed using a vapor deposition process utilizing a silicon precursor. Reference will be made herein. Figure 8 The method for forming silicon SCLs is described in more detail.
[0097] Silicon SCLs can include amorphous (e.g., non-crystalline) silicon. If (e.g., when) the silicon SCL is amorphous silicon, volume expansion during charging and discharging can be reduced compared to crystalline silicon, thereby further improving or enhancing the cycle life characteristics of rechargeable lithium batteries. Amorphous silicon can be identified by transmission electron microscopy (TEM) analysis and / or X-ray diffraction (XRD) analysis. For example, in TEM analysis, silicon in which no lattice fringes are observed can be referred to as amorphous (e.g., non-crystalline) silicon. As another example, silicon can be referred to as amorphous (e.g., non-crystalline) silicon if (e.g., when) broad peaks appear in XRD analysis using a CuKα radiation source.
[0098] As measured by X-ray diffraction analysis, silicon SCLs can have a grain size of about 4 nm or smaller. For example, the grain size of a silicon SCL can be about 3.5 nm or smaller, about 3 nm or smaller, about 2 nm or smaller, or about 1 nm or smaller. If (for example, when) the grain size of a silicon SCL exceeds about 4 nm, volume expansion during charging and discharging may increase, and cycle life characteristics may deteriorate. For example, if (for example, when) the grain size of a silicon SCL meets the aforementioned range, due to its low crystallinity, it can exhibit the effect of suppressing or reducing irreversible reactions, thereby improving or enhancing efficiency (e.g., initial efficiency) and cycle life characteristics.
[0099] In the present disclosure, the expression that the silicon SCL has a grain size of about 4 nm or less may mean that the silicon SCL can exhibit properties close to a fully (e.g., substantially fully) amorphous (e.g., non-crystalline) state, while locally having nanocrystallinity. In this case, the silicon SCL may exist in a mixed state of amorphous (e.g., non-crystalline) silicon and crystalline silicon. For example, the silicon SCL may be mainly (e.g., mostly or predominantly) composed of amorphous (e.g., non-crystalline) silicon, and may partially include crystalline silicon. However, in the present disclosure, for ease of description, even (e.g., when) silicon includes one or more nano-sized crystal grains, the silicon may also be referred to as amorphous (e.g., non-crystalline) silicon.
[0100] In one or more embodiments, if (e.g., when) the grain size of the silicon SCL is about 0 nm in X-ray diffraction (XRD) analysis, there is no regular crystal structure capable of defining a grain size, which may mean that the silicon SCL has a fully (e.g., substantially fully) non-crystalline state.
[0101] The grain size of the silicon SCL can be measured by X-ray diffraction (XRD) analysis. For example, in an X-ray diffraction spectrum using CuKα radiation with an X-ray wavelength of 1.541 Å, the grain size of the silicon SCL can be calculated by the Scherrer equation based on the full width at half maximum (FWHM) of the Si (111) peak.
[0102] The grain size of the silicon SCL can be measured by the following Equation 1.
[0103] Equation 1 L=0.9λ / βcosθ In Equation 1, L is the grain size (nm), λ is the X-ray wavelength (nm), β is the half width (rad) of the peak of the (111) plane of silicon, and θ is the diffraction angle (rad).
[0104] The silicon SCL may be formed on the pores POR and the surface of the porous carrier PMT. The nano-sized silicon SCL may be deposited in the pores POR of the porous carrier PMT by a vapor deposition process as described in one or more embodiments. Accordingly, silicon can be uniformly (e.g., substantially uniformly) distributed from the center of the porous carrier PMT toward the surface of the porous carrier PMT. In one or more embodiments, silicon may be naturally oxidized, and thus may be present in a trace amount in the negative electrode active material AM in the form of silicon oxide. For example, the core may further include silicon oxide (e.g., SiO on the pores POR and the surface of the porous carrier PMT x , where 0<x≤2; for example, SiO₂).
[0105] The amount of silicon SCL relative to the total weight of the negative electrode active material AM (e.g., based on 100 wt% of the negative electrode active material AM) can be from about 10 wt% to about 70 wt%. For example, the amount of silicon SCL relative to the total weight of the negative electrode active material AM (e.g., based on 100 wt% of the negative electrode active material AM) can be from about 20 wt% to about 60 wt%, from about 25 wt% to about 55 wt%, or from about 40 wt% to about 55 wt%.
[0106] If (for example, when) the silicon SCL is formed in a layer shape, the thickness of the silicon SCL can be greater than about 0 nm and less than or equal to about 10 nm. For example, the thickness of the silicon SCL can be about 0.5 nm or greater, about 1 nm or greater, or about 2 nm or greater. The thickness of the silicon SCL can be about 8 nm or less, about 6 nm or less, or about 4 nm or less. For example, the thickness of the silicon SCL can be the average thickness. As another example, if (for example, when) the silicon is non-uniformly formed, the thickness of the silicon SCL can be the length of the thickest location. The thickness of the silicon SCL can be measured by SEM and / or TEM images of a cross-section of the negative electrode active material AM. There are no particular limitations on the method used to measure the thickness of the silicon SCL, and any suitable method commonly used in the art can be used.
[0107] If (for example, when) one or more of a plurality of vias (PORs) are completely (e.g., substantially completely) filled with a silicon SCL, the diameter of the silicon SCL can be greater than about 0 nm and less than or equal to about 10 nm. For example, the diameter of the silicon SCL can be about 0.5 nm or greater, about 1 nm or greater, or about 2 nm or greater. The diameter of the silicon SCL can be about 8 nm or less, about 6 nm or less, or about 4 nm or less.
[0108] If (for example, when) the amount, thickness and / or diameter of the silicon SCL each meet the foregoing range, a rechargeable lithium battery with high capacity (e.g., electrical capacity) and improved or enhanced initial efficiency and cycle life characteristics can be provided.
[0109] Silicon undergoes volume expansion during charging and discharging, which can be a major cause of negative electrode degradation. According to one or more embodiments of this disclosure, because the silicon SCL is disposed within the pores (POR) of the porous carrier PMT, the size of the silicon SCL can be suitably or appropriately sized. For example, the negative electrode active material AM according to one or more embodiments of this disclosure can include nanoscale silicon within the pores (POR) of the porous carrier PMT, thereby effectively or appropriately suppressing or reducing silicon volume expansion while achieving its high capacity (e.g., charge) characteristics. As a result, rechargeable lithium batteries including the negative electrode active material AM according to one or more embodiments of this disclosure can exhibit excellent or suitable capacity (e.g., charge), efficiency (e.g., initial efficiency), and cycle life characteristics.
[0110] The negative electrode active material AM according to one or more embodiments of the present disclosure may include a carbon coating CTL (e.g., a shell) located on the core as described in one or more embodiments.
[0111] The carbon-coated CTL can surround (e.g., enclose) the surface of the core. The carbon-coated CTL can substantially completely surround (e.g., enclose) the surface of the core, or it can only partially surround (e.g., enclose) the surface.
[0112] The carbon coating CTL may include a second amorphous (e.g., non-crystalline) carbon. The second amorphous carbon may include at least one of soft carbon, hard carbon, mesophase pitch carbide, calcined coke, or any suitable combination thereof.
[0113] The amount of carbon coating CTL can be from about 0.1 wt% to about 10 wt% relative to the total weight of the negative electrode active material AM (e.g., based on 100 wt% of the negative electrode active material AM). For example, the amount of carbon coating CTL can be from about 0.1 wt% to about 8 wt%, from about 1 wt% to about 7 wt%, or from about 2 wt% to about 6 wt% relative to the total weight of the negative electrode active material AM (e.g., based on 100 wt% of the negative electrode active material AM).
[0114] The thickness of the carbon coating CTL can be from about 1 nm to about 100 nm. For example, the thickness of the carbon coating CTL can be from about 1 nm to about 50 nm, from about 1 nm to about 30 nm, or from about 1 nm to about 20 nm. If (for example, when) the thickness of the carbon coating CTL exceeds about 100 nm, the carbon coating CTL will act as or be used as a resistive layer, thereby causing a reduction in capacity (e.g., capacitance) and efficiency during charging and discharging. In this disclosure, the thickness of the carbon coating CTL can be measured by SEM and / or TEM images of a cross-section of the negative electrode active material AM. There are no particular limitations on the method used to measure the thickness of the carbon coating CTL, and it can be any suitable method commonly used in the art. For example, if (for example, when) amorphous (e.g., non-crystalline) carbon is not uniformly formed, the thickness of the carbon coating CTL can be the length of the thickest position. As another example, the thickness of the carbon coating CTL can be the average thickness.
[0115] If (for example, when) the amount and thickness of the carbon coating CTL both meet the aforementioned ranges, it is possible to maintain a structure with excellent or suitable hardness while minimizing or reducing irreversible reactions, and it is possible to further improve or enhance the initial efficiency and lifespan characteristics of rechargeable lithium batteries.
[0116] According to one or more embodiments of this disclosure, because the negative electrode active material AM includes a carbon-coated CTL, it is feasible to prevent (or reduce the degree or incidence of crack formation) within the particles during charging and discharging, thereby maintaining the particle morphology. In one or more embodiments, the presence of the carbon-coated CTL can prevent the multiple pores (POR) of the porous carrier PMT and the silicon SCL on the surface from being exposed to the outside (or reduce the degree or incidence of exposure of the multiple pores (POR) of the porous carrier PMT and the silicon SCL on the surface to the outside), thereby suppressing or reducing side reactions with the electrolyte. As a result, irreversible reactions can be minimized or reduced, and initial efficiency and cycle life characteristics can be further improved or enhanced.
[0117] As described in one or more embodiments, the negative electrode active material AM according to one or more embodiments of the present disclosure may have a structure in which silicon SCL is located on the surface of a porous carrier PMT and a plurality of pores POR, and carbon coating CTL is located on the porous carrier PMT on which silicon SCL is deposited.
[0118] The negative electrode active material AM can have a porous structure. For example, even when the silicon SCL is located on a porous support PMT, one or more empty spaces can be retained within multiple pores POR.
[0119] In one or more embodiments, one or more of the multiple pores (PORs) of the porous carrier PMT can be completely (e.g., substantially completely) filled with silicon SCL. For example, in the multiple pores (PORs) of the negative electrode active material AM, one or more pores can retain void space while the other pores can be substantially completely filled.
[0120] For example, because the silicon SCL is uniformly (e.g., substantially uniformly) deposited on the porous carrier PMT by a vapor deposition process as described in one or more embodiments, the internal space of relatively small micropores can be substantially completely filled by the silicon SCL. The internal space of relatively large mesopores or macropores can be partially filled by the silicon SCL. For example, one or more void spaces can remain in the internal space of mesopores or macropores.
[0121] According to one or more embodiments of this disclosure, the pore size distribution of the porous carrier PMT prior to the formation of the silicon SCL and carbon coating CTL may differ from the pore size distribution of the negative electrode active material AM after the formation of the silicon SCL and carbon coating CTL.
[0122] The volume ratio of mesopores in the negative electrode active material AM can be from about 50% to about 100% relative to the total pore volume (e.g., based on the total pore volume of the negative electrode active material AM). For example, the volume ratio of mesopores in the negative electrode active material AM can be from about 50% to about 95%, from about 50% to about 90%, or from about 50% to about 80% relative to the total pore volume of the negative electrode active material AM.
[0123] The micropore volume ratio of the negative electrode active material AM relative to the total pore volume can be about 20% or less. For example, the micropore volume ratio of the negative electrode active material AM can be about 15% or less, about 12% or less, or about 10% or less. The macropore volume ratio of the negative electrode active material AM relative to (e.g., based on) the total pore volume of the negative electrode active material AM can be about 50% or less. For example, the macropore volume ratio of the negative electrode active material AM can be about 10% to about 50%, about 10% to about 40%, or about 20% to about 40%. As described in one or more embodiments, the total pore volume of the negative electrode active material AM can be defined as the sum of the pore volumes of micropores, mesopores, and macropores within the negative electrode active material AM.
[0124] The pore volume of the negative electrode active material AM can be greater than approximately 0 cm³. 3 / g and less than or equal to approximately 0.1cm 3 / g. For example, the pore volume of the negative electrode active material AM can be approximately 0.001 cm³. 3 / g to approximately 0.05cm 3 / g, approximately 0.005cm3 / g to approximately 0.03cm 3 / g or approximately 0.005cm 3 / g to approximately 0.1cm 3 / g.
[0125] The average particle size of the negative electrode active material AM (in particulate form) can be approximately 1 μm to approximately 50 μm, approximately 1 μm to approximately 30 μm, or approximately 1 μm to approximately 20 μm. The average particle size can be the median diameter measured using a laser-type particle size analyzer.
[0126] Because the negative electrode active material AM comprises multiple pores (PORs), it is feasible to more effectively or appropriately suppress or reduce silicon volume expansion during charging and discharging. This can be because the multiple pores absorb the expanded volume, thus suppressing or reducing the overall volume expansion of the negative electrode active material AM. As a result, rechargeable lithium batteries comprising the negative electrode active material AM according to one or more embodiments of this disclosure can have excellent or suitable cycle life characteristics.
[0127] In the following, a method for manufacturing a negative electrode active material according to one or more embodiments of the present disclosure will be described in more detail.
[0128] Reference Figure 8 A method for manufacturing a negative electrode active material according to one or more embodiments of the present disclosure may include: preparing a porous support PMT comprising a plurality of pores; performing a vapor deposition process on the porous support PMT using a silicon precursor to form a silicon SCL; and forming a carbon coating CTL on the porous support on which silicon is formed using a carbon precursor. Therefore, the negative electrode active material according to one or more embodiments of the present disclosure can be manufactured by the manufacturing method as described in one or more embodiments.
[0129] First, a porous support PMT comprising multiple pore volumes (PORs) can be prepared. The porous support PMT can comprise amorphous (e.g., non-crystalline) carbon. The porous support PMT can comprise activated carbon, carbon nanotubes, carbon nanowires, graphene, carbon fibers, furnace black, carbon black, acetylene black, superconducting acetylene black, Ketjen black, or combinations thereof (e.g., any suitable combination), but there are no particular limitations on the type (variety) of the porous support PMT. For example, the porous support PMT can comprise commonly available or commonly used activated carbon. In this case, the porous support PMT can be appropriately or suitably selected and used to ensure (e.g., such that) the individual pore volume ratios satisfy the aforementioned range.
[0130] A porous carrier PMT may include multiple pores (PORs). The porous carrier PMT may include pores (PORs) having one or more suitable diameters, such as micropores, mesopores, or macropores. The volume ratio of micropores relative to (e.g., based on) the total pore volume may be from about 50% to about 100%. For example, the volume ratio of micropores may be from about 50% to about 90%, from about 50% to about 80%, or from about 50% to about 70%. The diameter of the micropores may be greater than about 0 nm and less than or equal to about 2 nm.
[0131] Subsequently, a vapor deposition process can be performed on the porous carrier PMT to form a silicon SCL. For example, a silicon SCL can be formed on the pores (POR) and surface of the porous carrier PMT using a vapor deposition process utilizing a silicon precursor.
[0132] The vapor deposition process can be a chemical vapor deposition (CVD) process and / or an atomic layer deposition (ALD) process. Chemical vapor deposition can include at least one of thermochemical vapor deposition, plasma-enhanced chemical vapor deposition, or low-pressure chemical vapor deposition.
[0133] Silicon precursors may include at least one of SiH4, Si2H6, Si3H8, SiCl4, or any suitable combination thereof. For example, silicon precursors may include SiH4.
[0134] Silicon SCLs can be deposited on the pores (POR) and surfaces of a porous substrate (PMT) using a vapor deposition process. As measured by X-ray diffraction analysis, silicon SCLs can have a grain size of approximately 4 nm or smaller. For example, the grain size of a silicon SCL can be approximately 3.5 nm or smaller, approximately 3 nm or smaller, approximately 2 nm or smaller, or approximately 1 nm or smaller.
[0135] The grain size of silicon SCLs can be controlled or selected by adjusting the pore structure of the porous carrier PMT. This is likely because the pore structure (e.g., the pore distribution by size) affects grain growth. If, for example, the volume ratio of micropores in the porous carrier PMT is less than about 50%, the density of crystal nucleation may be reduced because relatively large pores with small specific surface areas may occupy most of the total pore volume. In this case, there may be sufficient or suitable space for crystal growth, and thus large grains may form.
[0136] Conversely, if (for example, when) the volume ratio of the micropores in the porous carrier PMT meets the aforementioned range, the density of crystal nucleation can be increased because relatively small pores with large specific surface areas can occupy most of the total pore volume. In this case, the space available for crystal growth can be limited, thus suppressing or reducing grain formation, or allowing the formation of small grains.
[0137] In one or more embodiments, the grain size of silicon SCLs can be controlled or selected by adjusting process conditions such as heat treatment temperature and / or time in a vapor deposition process.
[0138] Vapor deposition processes can be performed at temperatures where the deposited silicon SCL can become amorphous (e.g., non-crystalline) silicon (a-Si). For example, vapor deposition processes can be performed at temperatures ranging from about 400°C to about 700°C. If, for example, the vapor deposition process is performed at temperatures above about 700°C, the deposited silicon SCL may become crystalline, thereby increasing volume expansion during charging and discharging and degrading cycle life characteristics. Conversely, if, for example, the vapor deposition process is performed at temperatures below about 400°C, the decomposition of the silicon precursor may occur insufficiently or inappropriately, and undecomposed silicon precursor, which may act as or serve as impurities, may remain within the porous carrier PMT. If, for example, the vapor deposition process is performed within the aforementioned temperature range, it is feasible to control the grain size of the silicon SCL within the aforementioned range. As a result, the effect of suppressing or reducing irreversible reactions can be achieved, thereby providing rechargeable lithium batteries with improved or enhanced efficiency and cycle life characteristics.
[0139] In the vapor deposition process, the flow rate of the silicon precursor gas can be from about 0.1 L / min to about 1 L / min or from about 0.1 L / min to about 0.5 L / min. The deposition time can be from about 0.5 hours to about 5 hours or from about 0.5 hours to about 3 hours. In the vapor deposition process, by appropriately or suitablely adjusting the gas flow rate and deposition time, silicon SCLs with desired or suitable amounts and grain sizes can be formed on a porous carrier PMT.
[0140] Then, a carbon coating CTL can be formed on the product on which silicon has been formed using a carbon precursor. The carbon coating CTL formation process can be performed by a vapor deposition process using a carbon precursor, or by mixing the obtained product with an amorphous (e.g., non-crystalline) carbon precursor and carbonizing it.
[0141] For example, carbon coatings (CTLs) can be formed using chemical vapor deposition (CVD) processes. CVD can include at least one of thermochemical vapor deposition (TCVD), plasma-enhanced chemical vapor deposition (PECVD), or low-pressure chemical vapor deposition (LPCVD).
[0142] The vapor deposition process can be carried out at temperatures of about 700°C to about 1000°C or about 700°C to about 950°C.
[0143] In vapor deposition processes, carbon gas can be used as a carbon precursor. Carbon gas may include at least one of methane (CH4), ethylene (C2H4), acetylene (C2H2), propane (C3H8), propylene (C3H6), or any suitable combination thereof.
[0144] In one or more embodiments, a carbon coating CTL can be formed by a process of mixing and carbonizing a carbon precursor. The carbon precursor can be converted into amorphous (e.g., non-crystalline) carbon by a carbonization process to form the carbon coating CTL.
[0145] The weight ratio of the product obtained by the silicon SCL formation process as described in one or more embodiments to the carbon precursor as described in one or more embodiments can be from about 99:1 to about 90:10. The carbon precursor can be provided in an appropriate or suitable amount so that (e.g., such that) the amount of carbon coating CTL in the finally manufactured negative electrode active material meets the desired or suitable range.
[0146] In the carbonization process, the carbon precursor may include at least one of petroleum bitumen, coal tar pitch, intermediate bitumen, bitumen carbon, synthetic bitumen, or any suitable combination thereof.
[0147] The carbonization process can be carried out at temperatures ranging from about 600°C to about 1,000°C or from about 700°C to about 1,000°C. Dispersants can be removed during the carbonization process. The carbonization process can be performed in an atmosphere of nitrogen, helium, or a combination thereof (e.g., any suitable combination).
[0148] Examples and comparative examples of this disclosure will be described in more detail below. However, the following examples are merely illustrative of this disclosure, and embodiments of this disclosure are not limited to these examples.
[0149] Example 1 Preparation of negative electrode active material Prepare a total pore volume of 0.8 cm³. 3 / g, and the volume ratios of micropores, mesopores, and macropores to the total pore volume are 60%, 30%, and 10%, respectively, of activated carbon porous carriers.
[0150] Amorphous (e.g., non-crystalline) silicon was formed on the pores and surface of a porous carrier by performing a chemical vapor deposition (CVD) process using SiH4 gas at 550 °C. In the CVD process, the SiH4 gas flow rate was 0.3 L / min, and the deposition was performed for 1 hour.
[0151] A carbon coating was formed on the surface of a porous silicon-based support by performing a chemical vapor deposition (CVD) process using C2H2 gas at 950°C. During the CVD process, the C2H2 gas flow rate was 0.3 L / min, and the deposition was performed for 1 hour.
[0152] The prepared negative electrode active material comprises a core containing silicon (e.g., amorphous (e.g., non-crystalline) silicon) located on the pores and surface of a porous support, and a carbon coating located on the core. At this point, relative to the total weight of the negative electrode active material (e.g., based on 100 wt% of the negative electrode active material), the amount of the porous support is 49 wt%, the amount of silicon is 48 wt%, and the amount of the carbon coating is 3 wt%. The grain size of the silicon included in the negative electrode active material is approximately 0 nm (e.g., the silicon included in the negative electrode active material is amorphous (e.g., non-crystalline) and does not exhibit a detectable grain size). This can be measured by X-ray diffraction analysis using CuKα rays. The diameter of the silicon in the negative electrode active material is 2 nm (e.g., the average grain size of silicon is approximately 2 nm, which refers to the size of a single silicon particle (or region) deposited onto the porous carbon support during the CVD process). The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0153] For example, as noted in more detail herein, the structural and compositional characteristics of the negative electrode active material prepared in Example 1—e.g., the high micropore volume of the porous carbon support, the deposition of ultrafine amorphous (e.g., non-crystalline) silicon particles with an average diameter of approximately 2 nm, and the conformal carbon coating—should collectively contribute to enhanced electrochemical performance. The amorphous nature of silicon (confirmed by the absence of detectable grain size via XRD analysis) should allow for improved or enhanced structural stability during lithiation and delithiation.
[0154] Manufacturing of half-cells The prepared negative electrode active material and natural graphite were mixed at a weight ratio of 15:85. A negative electrode active material slurry was prepared by mixing 97.5 wt% of the mixed negative electrode active material, 1.0 wt% of carboxymethyl cellulose, and 1.5 wt% of styrene-butadiene rubber in an aqueous solvent.
[0155] The negative electrode active material layer slurry is coated onto the Cu foil current collector, dried, and rolled to manufacture the negative electrode.
[0156] A half-cell was prepared by using a negative electrode, a lithium metal counter electrode, and an electrolyte. The electrolyte was a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 3:7) in which 1 M LiPF6 was dissolved.
[0157] Manufacturing of rechargeable lithium batteries By using 96wt% LiNi0.8 Co 0.1 Mn 0.1 A slurry for preparing the positive electrode active material layer was prepared by mixing O2 positive electrode active material, 2 wt% Ketjen black and 2 wt% polyvinylidene fluoride in N-methylpyrrolidone solvent.
[0158] The positive electrode active material layer slurry is coated onto the Al foil current collector, dried, and rolled to manufacture the positive electrode.
[0159] A rechargeable lithium battery (full cell) is manufactured using a negative electrode, a positive electrode, and an electrolyte. The electrolyte is a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 3:7) in which 1 M LiPF6 is dissolved.
[0160] Example 2 In addition to using a total pore volume of 0.85cm 3 The negative electrode active material was prepared in substantially the same manner as in Example 1, except for an activated carbon porous support with a volume ratio of 70%, 25%, and 5% of micropores, mesopores, and macropores to the total pore volume, respectively.
[0161] In the prepared negative electrode active material, the amount of porous support was 48 wt%, the amount of silicon was 49 wt%, and the amount of carbon coating was 3 wt%. The grain size of silicon included in the negative electrode active material was approximately 0 nm. The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0162] Except for using the negative electrode active material, the half-cell and rechargeable lithium battery are manufactured in essentially the same manner as in Example 1.
[0163] Example 3 In addition to using a total pore volume of 0.9 cm³ 3 The negative electrode active material was prepared in substantially the same manner as in Example 1, except for an activated carbon porous support with a volume ratio of 80%, 17%, and 3% of micropores, mesopores, and macropores to the total pore volume, respectively.
[0164] In the prepared negative electrode active material, the amount of porous support was 47 wt%, the amount of silicon was 50 wt%, and the amount of carbon coating was 3 wt%. The grain size of silicon included in the negative electrode active material was approximately 0.1 nm. The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0165] Except for using the negative electrode active material, the half-cell and rechargeable lithium battery are manufactured in essentially the same manner as in Example 1.
[0166] Example 4 In addition to using a total pore volume of 0.95 cm³ 3The negative electrode active material was prepared in substantially the same manner as in Example 1, except for an activated carbon porous support with a volume ratio of 90% for micropores and 10% for mesopores to total pore volume.
[0167] In the prepared negative electrode active material, the amount of porous support was 46 wt%, the amount of silicon was 51 wt%, and the amount of carbon coating was 3 wt%. The grain size of silicon included in the negative electrode active material was approximately 0.1 nm. The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0168] Except for using the negative electrode active material, the half-cell and rechargeable lithium battery are manufactured in essentially the same manner as in Example 1.
[0169] Comparison Example 1 In addition to using a total hole volume of 1.5cm 3 The negative electrode active material was prepared in substantially the same manner as in Example 1, except for an activated carbon porous support with a volume ratio of 10%, 80%, and 10% of micropores, mesopores, and macropores to the total pore volume, respectively.
[0170] In the prepared negative electrode active material, the amount of porous support was 40 wt%, the amount of silicon was 57 wt%, and the amount of carbon coating was 3 wt%. The grain size of silicon, including that in the negative electrode active material, was 9 nm. The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0171] Except for using the negative electrode active material, the half-cell and rechargeable lithium battery are manufactured in essentially the same manner as in Example 1.
[0172] Comparison Example 2 In addition to using a total pore volume of 1.15cm 3 The negative electrode active material was prepared in substantially the same manner as in Example 1, except for an activated carbon porous support with a volume ratio of 20%, 71%, and 9% of micropores, mesopores, and macropores to the total pore volume, respectively.
[0173] In the prepared negative electrode active material, the amount of porous support was 42 wt%, the amount of silicon was 55 wt%, and the amount of carbon coating was 3 wt%. The grain size of silicon included in the negative electrode active material was 6 nm. The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0174] Except for using the negative electrode active material, the half-cell and rechargeable lithium battery are manufactured in essentially the same manner as in Example 1.
[0175] Compare Example 3 In addition to using a total pore volume of 1.12 cm³ 3The negative electrode active material was prepared in substantially the same manner as in Example 1, except for an activated carbon porous support with a volume ratio of 30%, 65%, and 5% of micropores, mesopores, and macropores to the total pore volume, respectively.
[0176] In the prepared negative electrode active material, the amount of porous support was 43 wt%, the amount of silicon was 54 wt%, and the amount of carbon coating was 3 wt%. The grain size of silicon included in the negative electrode active material was 5 nm. The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0177] Except for using the negative electrode active material, the half-cell and rechargeable lithium battery are manufactured in essentially the same manner as in Example 1.
[0178] Compare Example 4 In addition to using a total pore volume of 1.10 cm³ 3 The negative electrode active material was prepared in substantially the same manner as in Example 1, except for an activated carbon porous support with a volume ratio of 40%, 55%, and 5% for micropores, mesopores, and macropores to the total pore volume, respectively.
[0179] In the prepared negative electrode active material, the amount of porous support was 44 wt%, the amount of silicon was 53 wt%, and the amount of carbon coating was 3 wt%. The grain size of silicon included in the negative electrode active material was 5 nm. The pore size distribution and pore volume of the negative electrode active material are shown in Table 1.
[0180] Except for using the negative electrode active material, the half-cell and rechargeable lithium battery are manufactured in essentially the same manner as in Example 1.
[0181] Evaluation Example 1: SEM Image Analysis of the Active Material of the Negative Electrode The surface and cross-sectional SEM images of the negative electrode active material according to Example 1 are shown below. Figure 9 , Figure 10A and Figure 10B middle.
[0182] Figure 10A It is a cross-sectional SEM image of the negative electrode active material based on Example 1. Figure 10B yes Figure 10A A magnified SEM image of region A of the negative electrode active material.
[0183] Reference Figure 9 , Figure 10A and Figure 10B It can be confirmed that the negative electrode active material according to Example 1 has a core-shell structure. It can be seen that the core includes a porous support (dark gray part) and silicon (light gray part) located in the pores and on the surface of the porous support, and the shell includes a carbon coating (light gray part) located on the core.
[0184] Evaluation Example 2: EDS mapping image analysis of the active material of the negative electrode A cross-section of the negative electrode prepared according to Example 1 was cut using a focused ion beam (FIB), and a portion of the cross-section was magnified for energy-dispersive X-ray spectroscopy (EDS) line scan analysis of the active material of the negative electrode. The distribution of carbon (C), silicon (Si), and oxygen (O) along the XY lines of the cross-section of the active material of the negative electrode was analyzed by EDS line scan analysis, and the results are shown in... Figure 11A and Figure 11B middle.
[0185] like Figure 11A and Figure 11B As shown, it can be seen that the negative electrode active material of Example 1 has silicon (Si) present in the pores and surface of the porous carrier. For example, it can be confirmed that the silicon (Si) is uniformly (e.g., substantially uniformly) distributed from the center of the porous carrier to the surface of the porous carrier PMT.
[0186] Evaluation Example 3: Porosity Evaluation of Porous Supports and Negative Electrode Active Materials For the porous supports of Examples 1 to 4 and Comparative Examples 1 to 4, pore size distribution (pore volume ratio) and pore volume were measured using a porosity analyzer (ASAP2020, Micromeritics) based on the Barrett-Joyner-Halenda (BJH) method and t-plot method. The results are shown in Table 1. The pore distribution of the porous support of Example 1 is shown in Table 1. Figure 12 middle.
[0187] For the negative electrode active materials according to Examples 1 to 4 and Comparative Examples 1 to 4, the pore size distribution (pore volume ratio) and pore volume were measured using a porosity analyzer (ASAP2020, Micromeritics) based on the Barrett-Joyner-Halenda (BJH) method and the t-plot method. The results are shown in Table 1. The pore distribution of the negative electrode active material according to Example 1 is shown in Table 1. Figure 12 middle.
[0188] Table 1
[0189] Evaluation Example 4: Specific Capacity Evaluation The half-cells according to Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged once at 0.1C, and their specific capacity was measured. The results are shown in Table 2.
[0190] Evaluation Example 5: Efficiency Evaluation The rechargeable lithium batteries of Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged once at 0.1C to determine the ratio of discharge capacity to charge capacity. The results are shown in Table 2 as efficiency.
[0191] Evaluation Example 6: Evaluation of Cyclic Expansion Rate The rechargeable lithium batteries according to Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to a formation process by charging and discharging once at 0.1C, and then charging and discharging 50 times at 1C. The ratio of the thickness of the rechargeable lithium battery after 50 charge and discharge cycles to the thickness of the rechargeable lithium battery before charging and discharging at 1C was determined. The results are shown in Table 2 as expansion rates.
[0192] Evaluation Example 7: Cycle Life Characteristic Evaluation The rechargeable lithium batteries according to Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged at 1C for 1000 or more cycles. The point at which the discharge capacity decreased sharply during the cycle was defined as the capacity degradation point, and the results are shown in Table 2. For each cycle, the capacity retention rate was calculated as the ratio of the discharge capacity of that cycle to the initial discharge capacity (cycle 1). The number of cycles at which the capacity retention rate reached 80% was defined as the cycle life degradation point, and the results are shown in Table 2.
[0193] Table 2
[0194] Referring to Table 2, it can be confirmed that Examples 1 to 4 have high capacity, low expansion rate, and excellent or suitable efficiency and cycle life characteristics.
[0195] Conversely, in the cases of Comparative Examples 1 to 4, which use porous carriers with low micropore volume ratios and excessively large silicon grain sizes, although excellent capacity was achieved, low efficiency and high expansion rates were observed, resulting in significant or substantial degradation of cycle life characteristics.
[0196] As a result, it can be seen that if (for example, when) a porous carrier according to one or more embodiments of the present disclosure is used and the grain size meets the range described in one or more embodiments, the efficiency, expansion characteristics and cycle life characteristics of the rechargeable lithium battery are improved or enhanced.
[0197] The negative electrode active material according to one or more embodiments of the present disclosure and the rechargeable lithium battery including the negative electrode active material may have excellent or suitable capacity (e.g., electrical capacity), efficiency and cycle life characteristics.
[0198] A method for manufacturing a negative electrode active material according to one or more embodiments of the present disclosure can produce a negative electrode active material having excellent or suitable capacity (e.g., capacitance), efficiency, and cycle life characteristics.
[0199] For example, comparative analyses between examples should demonstrate that the performance of negative electrode active materials is influenced by both (e.g., simultaneously) the pore structure of the porous support and the crystallinity of silicon. Examples utilizing porous supports with a high proportion of micropores (e.g., 60% or more) and silicon with amorphous or near-amorphous properties (e.g., grain size in the range of about 0 to about 0.1 nm) should produce excellent results in terms of initial efficiency, structural stability, and cycle life performance. Conversely, comparative examples with a lower micropore ratio and a larger silicon grain size (e.g., 5 nm–9 nm) exhibit reduced electrochemical performance (including reduced efficiency and poor capacity retention). These findings validate the crucial role of engineered pore structures and nanoscale amorphous (e.g., non-crystalline) silicon in achieving high-performance negative electrode active materials for rechargeable lithium-ion batteries.
[0200] Battery (e.g., rechargeable lithium battery) manufacturing apparatus, battery management system (BMS) device, and / or any other related device or component according to one or more embodiments of this disclosure can be implemented using any suitable hardware, firmware (e.g., application-specific integrated circuit), software, and / or combinations of software, firmware, and hardware (e.g., any suitable combination). For example, one or more suitable components of the device may be provided on an integrated circuit (IC) chip or on a separate IC chip. Furthermore, one or more suitable components of the device may be implemented on a flexible printed circuit film, tape-on-a-carrier package (TCP), printed circuit board (PCB), and / or disposed on a substrate. Additionally, one or more suitable components of the device may be a process or thread running on one or more processors in one or more computing devices, executing computer program instructions, and interacting with other system components to perform one or more suitable functions described herein. The computer program instructions are stored in memory, which may be implemented in a computing device using a standard memory device such as random access memory (RAM). The computer program instructions may also be stored in other non-transitory computer-readable media such as CD-ROMs, flash drives, etc. Furthermore, those skilled in the art will recognize that, without departing from the scope of this disclosure, the functions of one or more suitable computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed across one or more other computing devices.
[0201] In view of the whole of this disclosure, those skilled in the art will understand that each suitable feature of one or more embodiments of this disclosure may be combined in part or in whole or in combination with one another, and may be technically interlocked and operated in one or more suitable ways, and each embodiment may be implemented independently or in combination with one another in any suitable way, unless otherwise stated or implied.
[0202] While the subject matter of this disclosure has been described in conjunction with what are now considered practical exemplary embodiments, it will be understood that this disclosure is not limited to the disclosed embodiments, but is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the appended claims and their equivalents in one or more embodiments. Therefore, it will be understood that the one or more embodiments described herein are illustrative in all respects and not restrictive.
Claims
1. A negative electrode active material, said negative electrode active material comprising: nuclear; And a carbon coating, located on the core, The core includes: A porous support, comprising multiple pores and a first amorphous carbon; and Silicon, located on the surface of the plurality of pores and the porous carrier, and comprising amorphous silicon, and in, The plurality of pores includes micropores, and Based on the total pore volume of the porous carrier, the volume ratio of the micropores in the porous carrier is 50% to 100%.
2. The negative electrode active material according to claim 1, wherein, The first amorphous carbon includes at least one of activated carbon, carbon nanotubes, carbon nanowires, graphene, carbon fibers, furnace black, carbon black, acetylene black, superconducting acetylene black, Ketjen black, and combinations thereof.
3. The negative electrode active material according to claim 1, wherein, The diameter of the micropores in the porous carrier is greater than 0 nm and less than or equal to 2 nm.
4. The negative electrode active material according to claim 1, wherein, The average pore size of the porous carrier is greater than 0 and less than or equal to 10 nm.
5. The negative electrode active material according to claim 1, wherein, The total pore volume of the porous carrier is 0.5 cm³. 3 / g to 1cm 3 / g.
6. The negative electrode active material according to claim 1, wherein, Based on 100 wt% of the negative electrode active material, the amount of the porous support is 30 wt% to 80 wt%.
7. The negative electrode active material according to claim 1, wherein, The silicon is uniformly distributed from the center of the porous carrier toward the surface of the porous carrier.
8. The negative electrode active material according to claim 1, wherein, The silicon has a grain size of 4 nm or smaller, as measured by X-ray diffraction.
9. The negative electrode active material according to claim 1, wherein, Based on 100 wt% of the negative electrode active material, the amount of silicon is from 10 wt% to 70 wt%.
10. The negative electrode active material according to claim 1, wherein, The carbon coating comprises a second amorphous carbon, and The second amorphous carbon includes at least one of soft carbon, hard carbon, mesophase pitch carbide, calcined coke, and combinations thereof.
11. The negative electrode active material according to claim 1, wherein, The amount of carbon coating is from 0.1 wt% to 10 wt%, based on 100 wt% of the negative electrode active material.
12. The negative electrode active material according to claim 1, wherein, The thickness of the carbon coating is from 1 nm to 100 nm.
13. The negative electrode active material according to claim 1, wherein, The plurality of holes also includes mesopores, and Wherein, based on the total pore volume of the porous carrier, the mesopore volume ratio of the porous carrier is 40% or less.
14. A negative electrode, the negative electrode comprising: Negative electrode current collector; as well as A negative electrode active material layer is present on the negative electrode current collector and includes the negative electrode active material. The negative electrode active material includes a core and a carbon coating on the core. The core includes: Porous carrier, comprising multiple pores; and Silicon is located on the surface of the plurality of pores and the porous carrier, and in, The negative electrode active material also includes mesopores, and Based on the total pore volume of the negative electrode active material, the volume ratio of mesopores in the negative electrode active material is 50% to 100%.
15. The negative electrode according to claim 14, wherein, The negative electrode active material also includes micropores, and Wherein, based on the total pore volume of the negative electrode active material, the volume ratio of the micropores of the negative electrode active material is 20% or less.
16. The negative electrode according to claim 14, wherein, The total pore volume of the negative electrode active material is greater than 0 cm³. 3 / g and less than or equal to 0.1cm 3 / g.
17. A method, the method comprising: Prepare a porous carrier with multiple pores; Silicon is formed by performing a vapor deposition process on the porous carrier using a silicon precursor. as well as A carbon coating is formed on the porous carrier having silicon on it using a carbon precursor. in, The plurality of pores includes micropores, and Based on the total pore volume of the porous carrier, the volume ratio of the micropores in the porous carrier is 50% to 100%, and The method described herein is a method for manufacturing negative electrode active materials.
18. The method according to claim 17, wherein, The total pore volume of the porous carrier is 0.5 cm³. 3 / g to 1cm 3 / g.
19. The method of claim 17, wherein, The vapor deposition process is performed at a temperature ranging from 400°C to 700°C, and The silicon precursor includes at least one of SiH4, Si2H6, Si3H8, SiCl4, and combinations thereof.
20. The method of claim 17, wherein, The carbon precursor includes at least one of methane, ethylene, acetylene, propane, propylene, and combinations thereof.
Citation Information
Patent Citations
Differential pressure sensors for dynamic, high pressure, hydraulic systems
KR1020250045483A